A multiscale investigation on the performance improvement of fiber-reinforced cementitious composites after exposure to high temperatures. (October 2022) - Soares Junior, Paulo Roberto Ribeiro; Maciel, Priscila de Souza; Corrêa, Elaine Carballo Siqueira; Bezerra, Augusto Cesar da Silva
Abstract: Many studies on cement-based materials have addressed their deterioration at high temperatures. However, improvements in the performance of fiber-reinforced cementitious composites (FRCCs) have been observed after exposure to temperatures between 200 and 400 °C. This behavior needs to be further investigated as existing studies have primarily investigated the degradation of properties, without a focus on optimization. Hence, this study systematically investigated the FRCC performance improvement after exposure to high temperatures through a multiscale perspective, from the global behavior to the microstructure. The results showed that heat treatment improved the flexural behavior of the FRCC, mainly its strength and energy absorption capacity. The compressive and flexural strengths of the non-fibrous matrix also increased. The increments in the load and energy of fiber pull-out indicated that the fiber-matrix bonding was improved. A microstructural investigation confirmed an intact fiber-matrix interface and a cohesive cementitious matrix. Additionally, the main mechanisms of this enhanced behavior were related to matrix densification, interface optimization, and fiber clamping. These aspects, acting synergistically, promote a more effective interconnection between the composite components, improving the residual performance. Graphical abstract: Image 1 Highlights: The heat treatment (HT) at 260 °C improved the performance of FRCC. Increases in pull-out load and energy indicated a more effective fiber-matrix bonding. Microstructural investigation by SEM/OM revealed a cohesive interface and dense matrix. Matrix densification, interface optimization and fibers clamping can explain the HT-performance. A multiscale analysis contributes to explain the behavior of the composite.